Clinical Characteristics and Microbiological Profiles of Community-Acquired Intra-Abdominal Infections - Nata Pratama Hardjo Lugito; Cucunawangsih Cucunawangsih; Andree Kurniawan; Margaret Merlyn Tjiang (The Indonesian Society for Digestive Endoscopy, 2014)
Background: Intra-abdominal infections (IAIs) have different aspects to consider. One important aspectis the microbiological analyses, especially in the era of broad spread of resistant microorganisms. The studywas designed to describe the clinical characteristics and microbiological profiles of community acquired IAIs. Method: An observational study was performed on medical records of 12 months period (January toDecember 2013) in a General Hospital, Karawaci, Tangerang. Adult patients undergoing surgery for IAIs with positive microbiological culture and identification of microorganisms were included. Data collected were clinical characteristics and microbiological profiles and wereanalyzed statisticallyusing the SPSS version 17. Results: In 12 months period of study, 17 patients of IAIs with a total of 17 intra peritoneal specimens were collected. A total of six microorganisms were cultured. All the IAIs were monomicrobial, with aerobicmicroorganism dominantly Gram-negative bacilli. The dominant microorganism was Escherichia coli (E.coli), found in 58.8% of IAIs. The most common site was appendix (41.2%), and none from small intestine. Thesusceptibility test found that piperacillin tazobactam, tigecycline, meropenem and amikacin were the most activeantimicrobial against E. coli. Multi-drug resistant (MDR) E. coli in this study was 40%. The MDR E. coli had66.6% resistance to levofloxacin and ciprofloxacin, 66.6% susceptibility to ceftriaxone and ceftazidime, and100.0% susceptibility to amikacin. Conclusion: The most common site of community-acquired IAIs was appendix (41.2%). E. coli is still adominant microorganism with the MDR E. coli proportion of 40%.Keywords: intra-abdominal infections, clinical characteristics, microbiological profiles